2016
DOI: 10.1021/acs.est.5b04366
|View full text |Cite
|
Sign up to set email alerts
|

Development and Characterization of Ultrafiltration TiO2 Magnéli Phase Reactive Electrochemical Membranes

Abstract: This research focused on the synthesis, characterization, and performance testing of a novel Magnéli phase (TinO2n-1), n = 4 to 6, reactive electrochemical membrane (REM) for water treatment. The REMs were synthesized from tubular asymmetric TiO2 ultrafiltration membranes, and optimal reactivity was achieved for REMs composed of high purity Ti4O7. Probe molecules were used to assess outer-sphere charge transfer (Fe(CN)6(4-)) and organic compound oxidation through both direct oxidation (oxalic acid) and formati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
127
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 192 publications
(138 citation statements)
references
References 48 publications
10
127
1
Order By: Relevance
“…Similar flux (3208 L m À2 h À1 bar À1 ) was obtained by Guo et al (2016) with TiO 2 membranes reduced to Ti 4 O 7 using a thermal method at 1050 C under 1 atm H 2 during 50 h . The median pore size diameter of these membranes was 2.99 mm, however, the 70 mm thick active layer with smaller pores could not be characterized by Hg porosimetry.…”
supporting
confidence: 71%
See 4 more Smart Citations
“…Similar flux (3208 L m À2 h À1 bar À1 ) was obtained by Guo et al (2016) with TiO 2 membranes reduced to Ti 4 O 7 using a thermal method at 1050 C under 1 atm H 2 during 50 h . The median pore size diameter of these membranes was 2.99 mm, however, the 70 mm thick active layer with smaller pores could not be characterized by Hg porosimetry.…”
supporting
confidence: 71%
“…High permeate fluxes increased O 2 gas bubbles sweeping from the REM surface, thus resulting in the promotion of the competitive reaction of oxygen evolution. Guo et al (2016) reported the same behavior in a crossflow filtration configuration using TiO x REM from thermal reduction of TiO 2 under H 2 . Lower TOC removal rate (9.6 g m À2 h À1 ) but higher MCE (84%) was achieved for an optimal value of OA flux of 13.5 g m…”
Section: Electrochemical Oxidation Of Organic Compoundsmentioning
confidence: 56%
See 3 more Smart Citations